Comparison of Methods for Isolation and Characterization of Total and Astrocyte‐Enriched Extracellular Vesicles From Human Serum and Plasma - Leandra K. Figueroa‐Hall; Kaiping Burrows; Ahlam M. Alarbi; Bethany N. Hannafon; Cole Hladik; Chibing Tan; Rajagopal Ramesh; Jennifer L. Stewart; Victoria B. Risbrough; Martin P. Paulus; T. Kent Teague (Journal of Extracellular Biology, 2025)
ABSTRACT Extracellular vesicles (EV) which play critical roles in intercellular communication, have garnered interest as biomarkers with researchers studying brain‐related disease processes due to their ability to be isolated from various biofluids. Astrocytes, a type of glial cell, play a critical role in neuronal regulation and function. As such, EV enriched from astrocytes can be used to interrogate cargo and identify mechanisms by which astrocytes communicate with other cells of the central nervous system or shed light on pathophysiological conditions. This manuscript compared five EV isolation methods (differential ultracentrifugation [dUC], precipitation, precipitation + purification, silicon carbon resin and size exclusion chromatography [SEC]) using small volumes of human plasma and serum with a focus on immunocapture of astrocyte‐enriched EV (AEEV), with the excitatory amino acid transporter 1, or GLAST. Methods were evaluated on yield, purity, recovery and downstream application to include immunoassays for tetraspanin, immune and astrocyte markers. Results revealed that whilst precipitation‐based methods such as ExoQuick yielded higher EV concentrations, size exclusion (SmartSEC, qEV) provided greater purity, emphasizing a trade‐off between yield and purity. This study provides a comprehensive resource for researchers in selecting EV isolation methods tailored to small biobanked clinical samples, with the goal of advancing biomarker discovery in Neuroscience.